PERAN LANDASAN HUKUM AGAMA DALAM PRAKTIK MANAJEMEN RISIKO KONTEMPORER - Tiara Devi Yanti Lestari; Arsyadona; Nazwa Amelia Rangkuti; Rini Andrians; M Abiyyu wadi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
In an increasingly complex environment, risk management becomes an important part of organizational management. In the contemporary era, the application of risk management does not only focus on economic aspects, but also involves moral and spiritual values, especially in sharia-based organizations. Therefore, this research aims to explain how the basis of religious law can function as an ethical framework in risk management practices, especially in the context of Islamic banking. Religious principles, such as honesty, prudence and responsibility, contribute to establishing more ethical and sustainable risk management. The method used is library research with qualitative analysis of secondary data from various related literature. The research results show that religious legal foundations have an important role in risk management in sharia-based institutions. Concepts such as maslahah, gharar, and ihtiyat in Islam provide guidelines for organizations to carry out more responsible risk management practices, in accordance with sharia principles.